A new approach for supplier selection using fuzzy MCDM. Issue 1 (1st January 2014) - Rostamzadeh, Reza
The aim of this paper is to propose a new framework for supplier selection using FAHP and TOPSIS methods. As the human decision-making process usually contains fuzziness and vagueness, so linguistic values are used to assess the ratings and weights for criteria. A hierarchy multiple criteria decision-making (MCDM) model based on fuzzy-sets theory including FAHP adopted for finding weights of criteria and its sub-criteria and then for the final ranking of the suppliers TOPSIS method is used in a real industry case. This study concluded that the ranking of the main criteria and sub-criteria in all the suppliers are the same. Drawing on a real case, supplier A was identified to be the best supplier. Also, it can be said that TOPSIS method is a useful additional tool for the problem. More research is definitely called for within the context of studying a more complex supply chain with multiple supply network and nodes. There is also a crucial need for investigating other hybrid methods to find the optimum supplier. The proposed criteria can be applied both in industrial and service organisations with slight modifications.